Impact of the F508del mutation on ovine CFTR, a Cl− channel with enhanced conductance and ATP‐dependent gating. (9th April 2015) - Cai, Zhiwei; Palmai‐Pallag, Timea; Khuituan, Pissared; Mutolo, Michael J.; Boinot, Clément; Liu, Beihui; Scott‐Ward, Toby S.; Callebaut, Isabelle; Harris, Ann; Sheppard, David N.
Abstract : Key points: Malfunction of the cystic fibrosis transmembrane conductance regulator (CFTR), a gated pathway for chloride movement, causes the common life‐shortening genetic disease cystic fibrosis (CF). Towards the development of a sheep model of CF, we have investigated the function of sheep CFTR. We found that sheep CFTR was noticeably more active than human CFTR, while the most common CF mutation, F508del, had reduced impact on sheep CFTR function. Our results demonstrate that subtle changes in protein structure have marked effects on CFTR function and the consequences of the CF mutation F508del. Abstract: Cross‐species comparative studies are a powerful approach to understanding the epithelial Cl − channel cystic fibrosis transmembrane conductance regulator (CFTR), which is defective in the genetic disease cystic fibrosis (CF). Here, we investigate the single‐channel behaviour of ovine CFTR and the impact of the most common CF mutation, F508del‐CFTR, using excised inside‐out membrane patches from transiently transfected CHO cells. Like human CFTR, ovine CFTR formed a weakly inwardly rectifying Cl − channel regulated by PKA‐dependent phosphorylation, inhibited by the open‐channel blocker glibenclamide. However, for three reasons, ovine CFTR was noticeably more active than human CFTR. First, single‐channel conductance was increased. Second, open probability was augmented because the frequency and duration of channel openings were increased. Third, with enhanced affinity and efficacy, ATP more strongly stimulated ovine CFTR channel gating. Consistent with these data, the CFTR modulator phloxine B failed to potentiate ovine CFTR Cl − currents. Similar to its impact on human CFTR, the F508del mutation caused a temperature‐sensitive folding defect, which disrupted ovine CFTR protein processing and reduced membrane stability. However, the F508del mutation had reduced impact on ovine CFTR channel gating in contrast to its marked effects on human CFTR. We conclude that ovine CFTR forms a regulated Cl − channel with enhanced conductance and ATP‐dependent channel gating. This phylogenetic analysis of CFTR structure and function demonstrates that subtle changes in structure have pronounced effects on channel function and the consequences of the CF mutation F508del.